Klastering Industri Kecil Dan Menengah Di Kecamatan Gebog Kabupaten Kudus Menggunakan Sistem Informasi Geografis - Arif Setiawan; Pratomo Setiaji (Jurnal Sains dan Teknologi, 2014)
Research by title geographic information system clustering of small and medium industries in the sub district gebog Holy done in order to provide a reference to the Holy District Government , in developing small and medium industries in the district Gebog . Geographic Information System industry clustering in the district gebog mapped based on location , mapping industry in the district Gebok first step in the development of small and medium industries in all regions of the Holy , where the industry will be grouped based on the number of business units , total employment , and investment value . The method used in this study is to map the industry small and medium industries in the district area Gebog , the data used in this study is the data Gebog industry in the district . Bearing and distance retrieved from the zero point is square - the main sanctuary . The results of this study is a map -based information systems , and displays information on the number of business units , the amount of labor and the value of the investment industry in the district gebog .